2023
DOI: 10.3390/polym15030595
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Characterization of Core-Shell Structured Poly(vinylidene fluoride)-grafted-BaTiO3 Nanocomposites

Abstract: Dielectric properties of poly(vinylidene fluoride)-grafted-BaTiO3 (PVDF-g-BT) core-shell structured nanocomposites obtained from Reversible Addition Fragmentation chain Transfer (RAFT) polymerization of VDF were investigated by Broadband Dielectric Spectroscopy (BDS). The dielectric constant increased along with the BT content, about +50% by addition of 15 vol% of BT, which was around 40% more than expected from predictions using the usual dielectric modeling methods for composite materials, to be ascribed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
(91 reference statements)
2
10
0
Order By: Relevance
“…The high surface energy and large specific surface area of ceramic nanoparticles cause aggregation in the polymer matrix, giving rise to electron conduction with considerable dielectric loss, poor breakdown strength, and other deteriorated electrical properties. To achieve homogeneous nanoparticle dispersion, surface modification of ceramic nanoparticles based on the grafting from strategy (section ) has been shown as a powerful tool. , …”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The high surface energy and large specific surface area of ceramic nanoparticles cause aggregation in the polymer matrix, giving rise to electron conduction with considerable dielectric loss, poor breakdown strength, and other deteriorated electrical properties. To achieve homogeneous nanoparticle dispersion, surface modification of ceramic nanoparticles based on the grafting from strategy (section ) has been shown as a powerful tool. , …”
Section: Applicationsmentioning
confidence: 99%
“…With PVDF@BaTiO 3 made via SI-RAFT polymerization, Raihane et al reported that the core–shell FPNPs provide enhanced dielectric permittivity of about 50% higher than the prediction of the nanocomposite based on the Maxwell Garnett dielectric model, suggesting the promising PVDF/BaTiO 3 interface achieved by grafting from polymerization.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be attributed to the fact that the nanofiller can promote the nucleation of PPS [36,37]. As the concentration of G-ZnO increases, the number of nuclei increases, which increases the crystallization rate but hinders the growth of nuclei, resulting in smaller crystalline sizes [38,39]. As a result, PPS/G-ZnO nanocomposites are more likely to melt at lower temperatures during the heating process.…”
Section: Dsc Analysismentioning
confidence: 99%